2015
DOI: 10.1016/j.jdent.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between responses to questionnaire scenarios and actual treatment to repair or replace dental restorations in the National Dental PBRN

Abstract: Objective To quantify the agreement between treatment recommended during hypothetical clinical scenarios and actual treatment provided in comparable clinical circumstances. Methods A total of 193 practitioners in the National Dental Practice-Based Research Network participated in both a questionnaire and a clinical study. The questionnaire included three hypothetical scenarios about treatment of existing restorations. Clinicians then participated in a clinical study about repair or replacement of existing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The second limitation is the nature of nonvalidated self-reports that may not reflect the actual behaviour. However, a relatively recent study has shown that there is a high concordance between questionnaire responses and actual treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation is the nature of nonvalidated self-reports that may not reflect the actual behaviour. However, a relatively recent study has shown that there is a high concordance between questionnaire responses and actual treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this proportion of rural dentists was slightly less than previous HRSA estimates of the percentage of dentists practicing in rural areas (14%), it was consistent with other national estimates and the National Dental PBRN representation of rural dentists (and Funkhouser E, Barna J, Durand S, et al, unpublished data, 2019). Finally, although several National Dental PBRN studies demonstrate that member dentists report patterns of diagnosis and treatment that are similar to patterns of nonmember dentists, dentists who enroll in the National Dental PBRN may have key differences from nonenrolled dentists that may impact generalizability of findings …”
Section: Discussionmentioning
confidence: 99%
“…Finally, although several National Dental PBRN studies demonstrate that member dentists report patterns of diagnosis and treatment that are similar to patterns of nonmember dentists, dentists who enroll in the National Dental PBRN may have key differences from nonenrolled dentists that may impact generalizability of findings. [34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…Still, the baseline percentage of correct assignments of 30% revealed the lack of familiarity with systematic criteria. Other studies have highlighted the disparity in dentists' decisions with respect to their diagnostic measures 17 and restorative treatment decisions 10,19 . Regardless, most students had to decide whether to maintain a dental restoration at least once a month in their practice routine.…”
Section: Discussionmentioning
confidence: 99%
“…It is common for a clinician to decide the replacement of the restoration when he or she recognizes it as deviating from the ideal. For instance, the replacement of restorations is by far the most common restorative procedure and is driven mainly by the clinical diagnosis of caries 3 , despite the clinical judgment of the presence of caries being reported as highly inconsistent among dentists 10 .…”
Section: Introductionmentioning
confidence: 99%